Key concepts in mental health - Pilgrim, David 1950- (London Thousand Oaks, California SAGE, 2023)
This book includes "68 entries covering the breadth of past and contemporary understandings of mental health." It is an "introduction and reference for all professionals who have a stake in other people's mental health." -- from back cover.
Part IV: Mental health and society. Mental health policy -- Segregation -- Eugenics -- Capacity and culpability -- Anti-psychiatry -- Labeling theory -- Stigma -- Social and cultural capital -- Social exclusion -- Social networks and mental health -- Loneliness -- The mental health impact of social media -- Risks to and from people with mental health problems -- The mass media -- Social models of mental health -- Suicide -- Social class -- Race -- Gender/sex -- Age -- The pharmaceutical industry -- Warfare.
Previous edition: 2020.
Includes bibliographical references and index.
Keywords: Mental health services; Mental health; Social history; Mental Health Services -- organization & administration